Managing Pythium Blight in Overseeded Turf - Lawrence Datnoff; Carol Stiles; John Cisar (EDIS)
Pythium blight is a fast moving disease that can destroy an established grass stand within 24 hours after the first symptoms become visible, especially in a warm, humid environment. Typical initial symptoms include irregularly purplish to dark shaped areas, with a dark water-soaked appearance on the leaf blades. These leaves will become soft and slimy, mat together and eventually turn necrotic (brown), and die. Early in the morning or when the humidity is high, the leaves may be covered with white, cobwebby mycelium of the pathogen, Pythium aphanidermatum. This document is PP-66, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July, 2003.